Moderate and vigorous physical activity levels are associated with circulating CD34+ progenitor cells which are predictive of all-cause and cardiovascular mortality. (11th May 2021) - Ross, M; Muggeridge, D; Dodd, J
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Edinburgh Napier University Research Excellence Grant Background: Circulating progenitor cells (CPCs) play an important role in vascular repair and may influence cardiovascular (CV) health and longevity. Physical activity is known to promote vascular health and may do so by modulating CPC counts. Purpose: The primary aims of this study were to evaluate the association of CPCs with mortality and explore the association between physical activity (PA) and CPCs. Methods: We studied 1, 751 individuals from the Framingham Offspring cohort (66 ± 9 years, 54% female). CPCs (CD34+, CD34 + CD133+, CD34 + CD133 + KDR+) were measured from blood samples by flow cytometry. Multivariable cox regression analyses were performed to investigate the relationship of CPCs with future CV event, mortality, and all-cause mortality. Multivariate regression analyses were performed to determine the relationship between self-reported PA and CPC counts. Results: Following adjustment for standard risk factors, there was an inverse association between CD34+ CPCs and all-cause mortality (hazard ratio (HR) per unit increase in CD34+, 0.79; 95% CI 0.64 – 0.98). CD34 + CD133+ CPCs were inversely associated with CV mortality (HR 0.63, 95% CI 0.44 – 0.91, P = 0.013). Associations of CD34+ and CD34 + CD133+ with mortality were strongest in participants with pre-existing CVD. PA was associated with CD34+ CPCs only in CVD participants. This relationship was maintained after adjustment for confounding variables. Conclusions: Higher number of CD34+ and CD34+ CD133+ CPCs were inversely associated with all-cause and CV mortality. These associations were strongest in participants already diagnosed with CVD. PA is independently associated with CD34+ CPCs in individuals with CVD only, suggestive of greater benefit for this population group.